The Impact of Informativeness of Live Streaming in TikTok Live Shop Based on SOR Framework - Andrian Wijaya; Btari Mariska Purwaamijaya; Rangga Gelar Guntara (Indonesian Journal of Digital Business, 2024)
This research can be used as information related to digital marketing and provide awareness that the importance of informativeness can be crucial in increasing consumer purchase intentions through live streaming promotions on TikTok. Data analysis was performed by adopting Structural Equation Modelling (SEM) and testing the conceptual model using the Smart-PLS (v. 3.2.9) application. This method is suitable for analysing complex models with small sample sizes, such as exploring moderator and mediator effects in business and marketing. Stimulus (informativeness) has a strong role in influencing the formation of consumer attitudes towards influencers. Consumer attitudes towards influencers are said to support purchase intention. The influence is said to be sufficient to influence someone’s purchase intention. However, the stimulus (informativeness) does not have an influence on purchase intention if mediated by consumer attitudes towards influencers. The suggestion from this study is the need for research with focused subjects such as the content category to be studied, such as food, electronics, fashion, and others. Then respondents whose area is reduced, such as a regional part (province, city, district). It would also be interesting to research platforms other than TikTok Live Shop, such as YouTube Live Streaming, Twitch live streaming platform, and other platforms.